Ranking Load in Microgrid System Based on the Priority Weight Calculation of Power Supply - Nguyen, Thai An; Le, Trong Nghia; Quyen, Huy Anh; Pham, Hong Hau; Huynh, Thi Ngoc Thuong (Journal of Technical Education Science, 2022)
This paper proposes a method of ranking load in Microgird system based on the calculation of priority weights on the continuity of power supply of the loads. The proposed method applies the covariance matrix of the criterion layer to determine values of each criterion. The fuzzy preference relation matrix is used to replace the pairwise comparison matrix of the scheme layer. The weight of the criterion layer and the scheme layer are combined to get the final weights of each load bus. This solves the problem of consistency factor when evaluating loads from experts and Microgrid system operators. The calculation of priority weighting on the continuity of power supply for loads supports system operators to be proactive in planning load shedding or load shedding due to system failures, thereby minimizing damage to the system and electricity customers. The proposed method is calculated on the diagram of the IEEE 16 bus Microgrid system with six sources and eight loads.